Small-scale art organizations as participatory platforms for decolonizing practices and sensibilities. Issue 1 (1st January 2021) - Möntmann, Nina
ABSTRACT: The debate on restitution and other decolonizing practices of museums has been getting a lot of attention both in the public debate and in cultural studies. This essay shifts the focus to small-scale institutions and art spaces and their specific decolonizing practices and sensibilities. Unlike anthropological as well as art museums, which are dealing primarily with the politics of collecting, exhibition-making, provenance research, and restitution, smaller institutions and art spaces do not start out from the need to decentre collections and decolonize material objects. Instead, they work with artists, researchers, activists, and audiences to raise sensibilities, while discussing and experiencing how to relate to the history and current situation of a specific place in the context of a global colonial situation. Based on these practices of smaller organizations and their capacity to offer a platform for civic interests and participation, they suggest a dissent, a space of conflict, that, at a distance from the narrative of Western modernity, might reclaim futurity.